1974
DOI: 10.1073/pnas.71.12.5073
|View full text |Cite
|
Sign up to set email alerts
|

Development of Junctions During Differentiation of Lens Fibers

Abstract: Throughout the differentiation of eye lens epithelium into fibers, an extensive system of intercellular junctions develops. The junctional assembly is initially characterized by the accumulation of 9.0-nm intramombranous particles, forming linear rows in the matching plasma membranes of adjoining fibers. At the final stage of the fiber differentiation, the junctional particles are assembled in geometrically packed arrays.The formation of linear rows and bidiniensional lattices of intramembranous particles prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1977
1977
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…The main intrinsic protein MP26, the most abundant lens fiber cell membrane protein, has been proposed to be a candidate gap junction protein because both its developmental appearance and abundance correlate with the formation of fiber cell junctions (Benedetti, Dunia and Bloemendal, 1974 ;Goodenough, 1979). However, immuno-labeling studies have identified MP26 in both junctional and non-junctional regions of fiber cell plasma membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The main intrinsic protein MP26, the most abundant lens fiber cell membrane protein, has been proposed to be a candidate gap junction protein because both its developmental appearance and abundance correlate with the formation of fiber cell junctions (Benedetti, Dunia and Bloemendal, 1974 ;Goodenough, 1979). However, immuno-labeling studies have identified MP26 in both junctional and non-junctional regions of fiber cell plasma membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The unfixed specimens were fractured at -150'C. The replica was made immediately after the fracture by evaporation of platinum and carbon, using an electron gun (25). A Philips EM 400 microscope was used.…”
Section: Methodsmentioning
confidence: 99%
“…This pathway was distinct from gap junctions in that it was permeable to proteins and other macromolecules. Furthermore, it coupled only mature fibers in the lens, as opposed to gap junctions, which are present across the tissue (Benedetti et al, 1974). In the current study, we used a novel genetic approach to examine the exchange of macromolecules between cells in the mammalian lens.…”
mentioning
confidence: 99%